Perceived dental anxiety among schoolchildren treated through three caries removal approaches - Asli Topaloglu-Ak; Ece Eden; Jo E. Frencken (Journal of Applied Oral Science, 2007)
OBJECTIVES: The aim of the investigation was to test the differences in the perceived level of dental anxiety among children treated restoratively using the Atraumatic Restorative Treatment (ART) approach, the traditional restorative (TRA) approach and ART aided with a chemomechanical caries removal gel (ART plus). METHODS: The study subjects were 6-7-year-old children. TRA was compared to ART in a clinical setting after children had seen a dentist twice (Group A), ART was compared to 'ART plus' in a clinical setting after children had seen a dentist once (Group B) and ART was applied outside the clinic on school premises (Group C). The treatments were carried out in Class II cavitated dentine lesion in primary molars. Dental anxiety was measured using the Venham Picture Test (VPT). Three-way analysis of variances and interaction was applied to test for treatment approach, gender and operator effects on the mean VPT scores. RESULTS: There was no statistically significant difference (p=0.80) observed between the mean VPT scores for the traditional approach and those for the ART approach and between ART with and without a chemomechanical caries removal gel (p=0.07). Children in Group A had lower mean VPT scores than children in Group B (p=0.02) and Group C (p<0.00001) when treated using the ART approach by the same two operators. CONCLUSIONS: The level of dental anxiety was low. There was no difference in level of dental anxiety observed in children treated with ART in comparison to the traditional restorative approach, and between children treated with ART with and without a chemomechanical caries removal gel. The treatment environment and prepatory visits may be factors determining the level of dental anxiety in children treated through the ART approach only.